Eating disorder risk in adolescent and adult female athletes: the role of body satisfaction, sport type, BMI, level of competition, and training background - Borowiec, J.; Banio-Krajnik, A.; Malchrowicz-Mosko, E.; Kantanista, A. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Eating disorders negatively influence athletes` health and performance. To achieve a high level of performance and conform to cultural expectations regarding an athletic body type, female athletes often restrict their diets, which can lead to eating disorders. In addition to factors related to the sports environment, adolescent athletes are subject to changes caused by the maturation process. Therefore, the same factors may have different effects on eating disorder risk among adolescent and adult athletes. This study examined the relationship between eating disorder risk, specific aspects of the sports environment (sport type, level of competition [national and international], and training background), and individual aspects (body satisfaction and body mass index) in two groups of athletes: adolescents and adults.